Taguchi Method Approach To Plastic Bag Production: A Significant Efforts To Reduce Defects In The 24 Size Blowing Process - Ojakma Sihar Panaili Tumanggor; Sindhu Wismantoro; Kurniawan Agung; Edi Saneka (Journal of Innovative and Creativity, 2025)
The height level product defects​ pocket plastic Size 24 at CV. Prima Jaya Plasindo become problem main cause​ waste material standards and inefficiencies production . Research This aim identify and optimize production process parameters that contribute to disabled , with use Taguchi method . Four factors tested​ that is front , middle , and rear barrel temperatures , as well as anti- humidity dosage . Experimental design using Orthogonal Array L9(3^4) and analyzed with Signal to Noise Ratio (SNR) and Analysis of Variance (ANOVA) methods . The results show that the most significant factor influence disabled is front barrel temperature ( 65.46% contribution ), followed by anti- humidity ( 19.31%), middle barrel temperature (12.34%), and rear barrel temperature (0.83%). The optimal parameter combination obtained are A2 ( Rear Barrel Temperature 142°C), B1 ( Middle Barrel Temperature 145°C), C1 ( Front Barrel Temperature 148°C), and D1 ( Anti- Moisture Dosage 102 grams). Experiment confirmation show that average results and SNR values are within the confidence interval predictions , which prove validity results optimization . Research This succeed show that implementation Taguchi method in significant capable lower level defects , especially disabled spots white , in production process pocket plastic .